The Governance Divide in Global Corporate Responsibility: The Global Structuration of Reporting and Certification Frameworks, 1998–2017. Issue 6 (June 2020) - Pope, Shawn; Lim, Alwyn
In recent decades, as worldwide attention to corporate responsibility increased, the global corporate responsibility (GCR) movement did not converge on a singular governance model nor hybridize into myriad country-specific models. The movement, rather, bifurcated into onerous certification frameworks and more lax reporting frameworks. We examine this 'governance divide' in the GCR movement by investigating the cross-national diffusion of seven core GCR frameworks. We adopt a glocalization perspective that conceptualizes a vertical nesting of local and global contexts. Our cross-national quantitative analyses suggest that, while linkages to global culture have encouraged business participation in all GCR frameworks, power dependencies related to international trade and domestic factors related to effectiveness of local governance institutions have contributed to divergent diffusion patterns across reporting and certification frameworks. We discuss these findings in relation to several organizational perspectives and note their implications for further research on corporate responsibility.